ANALISIS GENDER UNTUK REKONSTRUKSI KEADILAN (Pengantar Pemahaman Relasi Gender dalam Keberislaman) - Imam Khanafi (Muwazah, 2009)
Justice is a purpose of universal humanity that must be continuously strugled to be realized in real world. There are many obstacle aspects in realizing it, among them is male oriented and patriarchy culture and customs. Justice bias based on those gender differences has rooted in human culture therefore it is regarded as a genuineness. This bias gender construct many aspects of life, including Islam. This research describe the root of general gender bias in Islam as the basic to reconstruct justice and gender equity in this life.